Unexplained Infant Deaths While on Propranolol for Treatment of Infantile Hemangiomas. Issue 1 (13th January 2022) - Pathman, Lydia; Dompmartin, Anne; Coquerel, Antoine; Robertson, Susan J.; Phillips, Roderic
Abstract : Propranolol is first-line systemic therapy for infantile hemangiomas. Its use in infants has significantly increased in the last decade. It has a good safety profile, but there are concerns about side effects. We present 5 unexplained deaths of infants who were on propranolol for treatment of infantile hemangiomas.